The Impact of Microfinance Institutions on Economic Growth A Literature Study in Indonesia - Sari, Yuli Indah; Chofifah, Diah Ismi (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the impact of Microfinance Institutions (MFI) on economic growth and financial inclusion in Indonesia. It explores how LKM supports Micro, Small, and Medium Enterprises (MSMEs) and low-income communities by providing accessible financing and financial literacy programs. Research Design & Methods: This study uses a qualitative method with a literature approach, which synthesizes existing studies on the role of MFIs in economic development. Relevant literature from peer-reviewed journals, government reports, and institutional studies are analyzed to identify key trends, challenges, and policy recommendations. Findings: The findings indicate that MFIs contribute significantly to MSME growth, job creation, and overall economic expansion by facilitating access to affordable credit and business support services. MFIs play a critical role in enhancing financial inclusion, especially in rural areas where formal banking services are limited. However, challenges such as limited capital, credit risk, and the evolving regulatory framework remain constraints to the sustainability of MFIs. Implications & Recommendations: To maximize the positive impact of MFIs, stronger collaboration between government, financial institutions, and business stakeholders is needed. A clear regulatory framework, increased accessibility of funding, and sustained financial literacy programs can enhance the effectiveness and long-term sustainability of MFIs. Contribution & Value Added: This study provides a comprehensive synthesis of the role of MFIs in the Indonesian economic landscape, highlighting both opportunities and challenges. By offering insights into best practices and policy recommendations, this study contributes to the ongoing discourse on financial inclusion and MSME development.